2015
DOI: 10.1080/10962247.2015.1067653
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol particulate matter in the Baltimore metropolitan area: Temporal variation over a six-year period

Abstract: This paper presents the first long-term aerosol speciation analysis in a Mid-Atlantic United States metropolitan area, which is essential for the air quality management agencies in order to revise regulations and reduce human exposure to adverse air quality conditions. The results suggest that although a declining trend in the overall PM2.5 was observed, no significant tendency was observed in the identified sources besides exceptional events such as the impact of wildfires on local air quality and downward co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…Previous studies have demonstrated that crustal elements (CEs: Fe, Ca, or Al) are the most abundant crustal metals in the background levels of surface alluvium soils (Kothai et al 2008;Kuo et al 2009;Hieu and Lee, 2007;Orozco et al 2015). The crustal elements constituted the majority of metallic element in alluvium soils along the Kaoping River in this study, which was similar to the metallic elements found in the alluvium soils distributed along the Jhuoshuei River in central Taiwan Kuo et al 2009;Taiwan EPA 2008).…”
Section: Metallic Composition Of Alluvium Soils In Kaoping Riversupporting
confidence: 76%
See 1 more Smart Citation
“…Previous studies have demonstrated that crustal elements (CEs: Fe, Ca, or Al) are the most abundant crustal metals in the background levels of surface alluvium soils (Kothai et al 2008;Kuo et al 2009;Hieu and Lee, 2007;Orozco et al 2015). The crustal elements constituted the majority of metallic element in alluvium soils along the Kaoping River in this study, which was similar to the metallic elements found in the alluvium soils distributed along the Jhuoshuei River in central Taiwan Kuo et al 2009;Taiwan EPA 2008).…”
Section: Metallic Composition Of Alluvium Soils In Kaoping Riversupporting
confidence: 76%
“…Fe was the most abundant metal found in the resuspension experiment. Relatively high contents of Fe 2.5 , ranging from 3,000 to 4,000 μg/g, and Fe 2.5-10, ranging from 6,500 to 9,800 μg/g, are not commonly observed in Earth crust (Kuo et al 2009;Mead, Herckes, and Majestic 2013), but might be attributed to anthropogenic contributors, such as iron-steel manufacturing and smeltery works (Tsai et al 2010;Orozco et al 2015). Notably, the largest and most active integrated steel mills are located in Hsiaokang District, southern Kaohsiung, about 10 km away from the Kaoping River.…”
Section: Metallic Composition Of Alluvium Soils In Kaoping Rivermentioning
confidence: 99%
“…One potential source that may contribute to the neurotoxic potential of pollution particulate is diesel exhaust particles. Diesel exhaust is a particular concern for public health as it is a substantial contributor to the ultrafine emission fraction on highways within the United States [1921]. Off- and on-road diesel emissions have been estimated to contribute > 50% of the ambient black carbon within the Los Angeles and San Francisco Bay Area in 2010 [22].…”
Section: Introductionmentioning
confidence: 99%
“…1). There are a variety of sources for PM exposure [97]. Recent studies showed that the median concentration of PM 2.5 in the smoking area (both indoor and outdoor) was significantly higher than in the control area [98][99][100].…”
Section: Pm and Stem Cellsmentioning
confidence: 99%